Prevalence of dental anomalies in different facial patterns and malocclusions in an Iranian population - Arman Mohammadi Shayan; Ahmad Behroozian; Amirhouman Sadrhaghighi; Saeid Foroughi Moghaddam; Aysan Shahmorad Moghanlou; Mahsa Amanabi (Elsevier, 2022)
Objective: This study aimed to evaluate the prevalence and association of dental anomalies with different types of malocclusions and facial patterns. Methods: In this cross-sectional study, the records of patients referred to the Orthodontics Department at 12-20 years of age were collected. The patients were classified into four types of malocclusion: Cl I, Cl II div 1, Cl II div 2, and Cl III, and three types of facial patterns: normal, long, and short. Fifteen dental anomalies were searched within the documents. The statistical analysis of data was performed with chi-squared and Fisher's exact test. Results: Among 602 patients evaluated in this study, 28.6% were males, and 71.4% were females. The prevalence of Cl I, Cl II div1, Cl II div 2, and Cl III was 58.3%, 28.7%, 5.5%, and 7.5%, respectively. The normal facial pattern was most prevalent (47.2%), followed by the long facial pattern (41.4%) and short facial pattern (11.5%); 60.7% of the study population had at least one dental anomaly. Dilaceration was the most common anomaly (27.7%), followed by impaction (21.8%) and hypodontia (18.9%). Most dental anomalies were found in females, Cl II malocclusion, and long face samples. A statistically significant association was found between transposition and male gender (P = 0.006) and between short roots and Cl II malocclusion (P = 0.047). No significant association was found between dental anomalies and facial patterns. Conclusion: Significant associations were reported between transposition and male gender and between short roots and Cl II malocclusion. In our population, dilaceration was the most common dental anomaly.